Risky business: a longitudinal study examining cigarette smoking initiation among susceptible and non-susceptible e-cigarette users in Canada - Aleyan, Sarah (BMJ Open, 2018)
OBJECTIVES: Given that many adolescent e-cigarette users are never-smokers, the possibility that e-cigarettes may act as a gateway to future cigarette smoking has been discussed in various studies. Longitudinal data are needed to explore the pathway between e-cigarette and cigarette use, particularly among different risk groups including susceptible and non-susceptible never-smokers. The objective of this study was to examine whether baseline use of e-cigarettes among a sample of never-smoking youth predicted cigarette smoking initiation over a 2-year period. DESIGN: Longitudinal cohort study. SETTING: 89 high schools across Ontario and Alberta, Canada. PARTICIPANTS: A sample of grade 9–11 never-smoking students at baseline (n=9501) who participated in the COMPASS study over 2 years. PRIMARY AND SECONDARY OUTCOME MEASURES: Participants completed in-class questionnaires that assessed smoking susceptibility and smoking initiation. RESULTS: Among the baseline sample of non-susceptible never-smokers, 45.2% of current e-cigarette users reported trying a cigarette after 2 years compared with 13.5% of non-current e-cigarette users. Among the baseline sample of susceptible never-smokers, 62.4% of current e-cigarette users reported trying a cigarette after 2 years compared with 36.1% of non-current e-cigarette users. Overall, current e-cigarette users were more likely to try a cigarette 2 years later. This association was stronger among the sample of non-susceptible never-smokers (AOR=5.28, 95% CI 2.81 to 9.94; p<0.0001) compared with susceptible never-smokers (AOR=2.78, 95% CI 1.84 to 4.20; p<0.0001). CONCLUSIONS: Findings from this large, longitudinal study support public health concerns that e-cigarette use may contribute to the development of a new population of cigarette smokers. They also support the notion that e-cigarettes are expanding the tobacco market by attracting low-risk youth who would otherwise be unlikely to initiate using cigarettes. Careful consideration will be needed in developing an appropriate regulatory framework that prevents e-cigarette use among youth.